Design of machinery : An introduction to the synthesis and analysis of mechanisms and machines - Norton, Robert L., ....- (Boston : McGraw-Hill, 2004)
Robert Norton's DESIGN OF MACHINERY 3/e continues the tradition of this bestselling book by emphasizing the design aspects of mechanisms and providing numerous industry examples and illustrations for readers. Norton provides a solid conceptual foundation for the kinematics and dynamics of machinery, presented in the context of what a design engineer needs to work with. The new 3/e has revised and expanded chapter problem set--231 new problems have been added. 88 Project Assignments are also included to give readers an in-depth look at mechanism design and analysis procedures in a realistic format. Coverage of compliant mechanisms and MEMS has been added in Chapter 2; a section entitled "Some Useful Mechanisms" is now in Chapter 3; treatment of cams in Chapters 8 has been condensed and modernized. Information on transmissions and engine dynamics has been enhanced and expanded as well. The third edition comes with a bound-in Student Resources CD-ROM, with Norton's own student-version programs, an extensive group of Working Model simulations (by Sid Wang, North Carolina A&T University), additional Working Model examples, and the MSC Working Model 2-D program itself (demonstration version). A new Book Website includes additional instructor and student resources. Detailed solutions to all chapter problems and project assignments, are available to instructors on the website, under password protection. --This text refers to the Hardcover </exec/obidos/tg/detail/-/0072864478/002-2421465-4632011?v=glance&s=books > edition
Keywords: Machines; Ontwerpen; Werktuigkundig ontwerpen